Stercoral Perforation Requiring Subtotal Colectomy in a Patient on Methadone Maintenance Therapy. (24th May 2012) - Sakharpe, A.; Lee, Y. K.; Park, G.; Dy, V.
Abstract : Stercoral perforation of the colon is a rare but serious complication of chronic constipation. We present a case of stercoral perforation requiring subtotal colectomy in a 41-year-old female who had been on methadone maintenance for a history of long-term intravenous heroin use. Our case highlights the importance of prompt and thorough surgical intervention in the successful treatment of this rare condition.